Self-Medication Pattern among Customers in a Community Pharmacy - Almasdy, Dedy (Fakultas Farmasi Universitas Andalas, 2023)
Self-medication is a common practice carried out by the community. This practice is increasingly popular due to the increasing number of OTC products being marketed and the increase in public knowledge due to advances in information technology. This cross-sectional research was conducted at a community pharmacy by collecting data using a structured interview approach to document self-medication practices carried out by customers. A total of 285 customers were interviewed. The Mean age was 30.54 years old. The majority of them were female (74.4%), students (57.2%), and had secondary-level education (72.3%). The majority of the customers came to the pharmacy to continue their medicines which were bought before the day of the visit (60.4%). The dominant factor that influenced the customers to buy the medicines was the experience of using previous medicines (34.9%). Related to a question about customer's adherence to drug regimen, the majority of them (71.5%) answered 'always' and 'often', meanwhile to question about customers' practice if the medicine could not produce the desired effect, the majority of them (75%) answered 'stopping the medicines and seeking professional advice's. The total number of medicines that were bought by the customers were 375 items (mean 1.27 + 0.51), consisting of scheduled poison medicines, OTC medicines, vitamin/mineral supplement, and phyto-medica.